Visible signs of ageing : representing older women in Australian popular fiction - Byrski, Elizabeth (Curtin University, 2009)
At the start of a new millennium, after thirty years of writing journalism and non-fiction, I began my first novel. I had always wanted to write fiction but the need to earn a living had kept me working to short deadlines with the reassurance of a pay cheque. It was when I was in my mid-fifties and searching for intelligent popular fiction featuring women of my own age as the central characters, that I drew a blank. This started me thinking; popular fiction was packed with younger women, but older women as central characters were noticeably absent, they were absent too from the other products of popular culture. As a freelance writer my first thought was that I had found a gap in the market that I might fill, but as time passed the project became more complex and, to me, much more important. Almost ten years have passed and I have now written five novels about the lives of older women all of which are Australian bestsellers; some are now published in France, Germany, Canada and Britain. This exegesis accompanies the five novels which I submit for examination for the degree of Doctor of Philosophy by Supplication. The exegesis links the novels and places them in the context of representations of ageing women in popular feminist fiction. While copies of all the novels are provided only Gang of Four (2004) and Bad Behaviour (2009), are required reading.This thesis documents my own journey as a writer and a feminist and explains how I moved from non-fiction and journalism to the novel to explore the lives of older women in twenty-first century Australia. In the first chapter I discuss ageism and the double standard of ageing applied to women, their invisibility and negative stereotypical representations in popular culture, and I consider fictional representations of women in classical and contemporary fiction. Chapter 2 explores women‘s relationship with fiction as readers, and the development of the consciousness raising feminist fiction of the late sixties and seventies. It also explores the relationship between feminism and consumer culture and the impact of post-feminism on women‘s fiction and on older women. In Chapter 3 I examine how these understandings informed the writing of the novels and compare them with second wave feminist realist fiction of the seventies. I argue that my texts can be read as a form of the feminist consciousness raising novel for older women in the twenty-first century.Throughout this thesis I have used the terms that are most widely used in studies of ageing to define age groups: the adjectives "older" and "ageing" denote women between the approximate ages of 50 – 65, while "old" and "aged" describe women of 65 years and over. For ease of reading and to reduce repetition I use the term ―consciousness raising‖ to describe a process, and the abbreviation "CR" to describe consciousness raising novels.